Penerapan Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar dan Minat Siswa Pada Materi Laju Reaksi Di SMA Katolik Medan XI IPA 4 - Ernita Purba; Rudi Munzirwan (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to determine: (1) Knowing the increase of learning outcomes of Trisakti Catholic High School students by applying the Problem Based Learning to the reaction rate material (2) Knowing the responses of Trisakti Catholic High School students by applying the Problem Based Learning on the subject of reaction rates. This type of research includes experimental research. This research was conducted at XI IPA Trisakti Catholic High School. The population in this study were students of class XI IPA Trisakti Catholic High School in the first semester of Academic year 2021 who were studying the reaction rates. The sample of this study was only taken one class where all students of XI IPA-4 Trisakti Catholic High School were 30 students. Sampling was done by purposive sampling method. The instruments used are test instruments to measure learning outcomes and non-test instruments to measure learning motivation. The analysis technique used the average test value, the percentage increase in learning outcomes, normality test, homogeneity test, hypothesis testing and gain test. The results obtained that the average value of the experimental class for pretest and posttest data was 57.25 and 83.5. The data on the normality and homogeneity test obtained data with normal distribution and homogeneous data. The results of the hypothesis test were carried out by testing the one sample t-test using a significant level of = 0.05, the thit value was 8.747. The Problem Based Learning developed on the subject of reaction rates is higher than the specified minimum completeness criteria (KKM) (KKM 70). The gain test was carried out with the N-Gain value of 81.82%, so it was included in the high category. It is proven that the chemistry learning outcomes of students who are taught using the Problem Based Learning developed on the subject of reaction rates make students learning outcomes increase